2017
DOI: 10.1177/0003319717715964
|View full text |Cite
|
Sign up to set email alerts
|

Increased Pulse Wave Velocity in Systemic Lupus Erythematosus: A Meta-Analysis

Abstract: Systemic lupus erythematosus (SLE) is associated with increased cardiovascular risk. This study aims to derive a more precise estimation on pulse wave velocity (PWV) level in patients with SLE and related factors. A literature search was performed using PubMed, EMBASE, and The Cochrane Library databases, studies published up to February 28, 2017, in English. Pooled standardized mean difference (SMD) with 95% confidence interval (CI) was calculated by fixed-effect or random-effect model analysis. Heterogeneity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 41 publications
1
19
0
1
Order By: Relevance
“…32 50,51 To date, at least 13 single-center cross-sectional studies 33 45 and 2 multicenter longitudinal studies 37,50,51 suggest that aortic stiffness and reflected waves are increased in adult patients with CD and UC, even after adjustment for known CV risk factors (Table 1) and that the severity and duration of inflammation over time has a key role in the arterial stiffening process. These results have been confirmed in 4 aggregated data 32,46,47,48 and 1 individual participant data meta-analysis 49 performed in patients with IBD, which are in agreement with similar findings reported in patients with rheumatoid arthritis, systemic lupus erythematosus, systemic sclerosis, and periodontitis 16 18,53 and could suggest that arterial stiffness is a vascular biomarker of chronic inflammation. 54 Further longitudinal studies are needed to confirm this hypothesis.…”
Section: Aortic Stiffness Is Increased In Ibd and In Patients With Chsupporting
confidence: 84%
See 1 more Smart Citation
“…32 50,51 To date, at least 13 single-center cross-sectional studies 33 45 and 2 multicenter longitudinal studies 37,50,51 suggest that aortic stiffness and reflected waves are increased in adult patients with CD and UC, even after adjustment for known CV risk factors (Table 1) and that the severity and duration of inflammation over time has a key role in the arterial stiffening process. These results have been confirmed in 4 aggregated data 32,46,47,48 and 1 individual participant data meta-analysis 49 performed in patients with IBD, which are in agreement with similar findings reported in patients with rheumatoid arthritis, systemic lupus erythematosus, systemic sclerosis, and periodontitis 16 18,53 and could suggest that arterial stiffness is a vascular biomarker of chronic inflammation. 54 Further longitudinal studies are needed to confirm this hypothesis.…”
Section: Aortic Stiffness Is Increased In Ibd and In Patients With Chsupporting
confidence: 84%
“…13 –15 Similar findings were reported in other chronic inflammatory conditions characterized by high levels of tumor necrosis factor (TNF), such as rheumatoid arthritis, systemic lupus erythematosus, systemic sclerosis, and chronic kidney disease. 16 19 Regarding treatment, steroids are associated with an increased risk of acute arterial events in IBD. 20 In contrast, other immunosuppressive drugs may lower the risk of acute arterial events due to their anti-inflammatory actions, as increasingly recommended in rheumatoid arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…However, this meta-analysis reported only 1 recognized marker (cIMT) of subclinical atherosclerosis, other surrogate markers, such as flow-mediated dilation (FMD%), carotid-femoral pulse wave velocity (cf-PWV), and glyceryl trinitrate-mediated dilatation (GTN%) were not evaluated. 24,25…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, other studies related increased cfPWV with SLE, low C3 complement levels and high CRP [22]. Recently, a meta-analysis of cfPWV studies in SLE patients concluded that cfPWV was increased vs CS [23]. In addition, in type 2 diabetes, it was explored the consequences of long term increased arterial stiffness on microvascular damage [24].…”
Section: Discussionmentioning
confidence: 99%